Transformasi Ruang Persampahan menjadi Ruang Penghidupan: Dinamika Ekonomi Informal di Sekitar TPA Cipayung - MOCH. ILHAM NOER SUNAN (Talenta usu, 2026)
This study aims to analyze how TPA Cipayung has transformed waste disposal space into a livelihood space and shaped the dynamics of the informal economy in surrounding communities. The study employed a descriptive qualitative approach. Data were collected through field observations, in-depth interviews, and documentation. The research involved six informants consisting of one employee of the Cipayung landfill management unit, two waste pickers, one waste collector, one small food stall owner, and one vehicle cleaning service provider. Data were analyzed through the stages of data reduction, data display, and conclusion drawing. The findings reveal that the landfill functions not only as a final disposal site for urban waste but also as a socio-economic space that creates livelihood opportunities for nearby residents. The daily flow of waste generates a chain of economic activities involving waste pickers, collectors, small traders, and supporting service providers. These activities form an informal economic network characterized by interdependent relationships among actors. In addition, local communities demonstrate adaptive livelihood strategies by utilizing economic opportunities available within the waste environment. The study highlights that urban waste management systems are not solely environmental issues, but are also closely related to the formation of local livelihood structures and social welfare.